Elemental design analysis on high rise buildings - Yong, Hui Lie, 1990-, author; Kherun Nita Ali, supervisor; Rosli Abdul Rashid, supervisor; Fakulti Alam Bina (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda (Ukur Bahan)) - Universiti Teknologi Malaysia, 2015